Assistance in Making NIB to Increase Micro, Small and Medium Enterprises (MSMEs) in Jajawar Village - Mubarrok, Dede Husni; Iswanto, Pepe; Maghfiroh, Harisatul; Lesmana, Soni Ardian; Fauzi, Fikri Muhammad (Khidmat, 2024)
This community service article focuses on efforts to strengthen awareness of the importance of financing Islamic madrasah education through community capacity building in Ciamis district and Banjar City, West Java Province. So far, society in general still prioritizes Islamic education, so that its management and financing is carried out as is without any effort to improve the management system and attention from the community. The service method is carried out using several techniques, namely conducting focus group discussions, workshops, and forming a Madrasah Diniyah support group (KPMD). After providing assistance and service, the results can be seen, including the emergence of public awareness of the importance of financing education for Diniyah Madrasahs and the formation of Madrasah Diniyah support groups consisting of community leaders, aghniya, ASN, entrepreneurs and other donors.